Keteladanan Kepemimpinan Paulus sebagai Strategi Teologi Pemimpin Kristen Era Digital dan Post Truth - Sumual, Elisa Nimbo; Arifianto, Yonatan Alex (Pusat Studi Pentakosta Indonesia, 2025)
Christian leadership in the digital age faces serious challenges due to the rapid flow of information, rapid social change, and the weakening of truth due to subjectivity in the midst of a post-truth culture. Moreover, Christian leaders are often caught up in digital image-building that is oriented towards popularity, thereby neglecting the spiritual dimension and role models that should be the basis of leadership. In this study, the exemplary nature of biblical figures is important as a foundation for a solid and relevant theology of leadership. Moreover, the phenomenon of hoaxes, ethical crises, and social polarisation further emphasises the need for Christian leadership and role models. This study aims to examine Paul's leadership example as a theological strategy for Christian leaders in facing the dynamics of the digital age. The study was conducted using a qualitative approach through literature review, leading to the conclusion that Paul's integrity is the theological foundation that strengthens Christian leadership in the digital age, because from it springs spiritual honesty that keeps leaders faithful to the Gospel. From this integrity, Paul's ministry presents a paradigm of transformative leadership that is relevant in the midst of a post-truth culture, while his perseverance in suffering sets an example of spiritual resilience for contextual Christian leaders. All of these examples emphasise the relevance of Paul's theological strategy for today's Christian leaders, namely to build leadership that is integrity-based, transformative, and resilient in facing the challenges of the digital age.